Bahasa Inggris - Florentina Kurniasari; Juvy Reyes (Ultima Management : Jurnal Ilmu Manajemen, 2020)
As a developing country, Indonesia needs capital flow from investment to support country’s development growth. Capital market is one form of source investment fund. Of the several indexes listed in Indonesia Stock Exchange, the LQ 45 Index is one of the indexes of concern to investors, in which banking is one of financial institution to support country’s economic development. Investors is concerned about the stock price volatility which is influenced by internal and external factors. In this research there are three internal factors and two external factors as independent variable. This research measured the stock price volatility by analyzing the effect of some factors including dividend yield, return on asset, asset growth, interest rate, and exchange rate of banking industries which registered in LQ 45 Index for year 2012 –2019. The data will be analyzed using multiple linear regression analysis model. The research shows that interest rate had positive influence on stock price volatility. While return on asset and exchange rate have negative effect to stock price volatility. Key Words: Stock Price Volatility, Dividend, ROA, Interest, Exchange Rate